Modulation of Working Memory Using Transcranial Electrical Stimulation: A Direct Comparison Between TACS and TDCS - Röhner, Franziska; Breitling, Carolin; Rufener, Katharina S.; Heinze, Hans-Jochen; Hinrichs, Hermann; Krauel, Kerstin; Sweeney-Reed, Catherine M. (Frontiers in Neuroscience, 2018)
Transcranial electrical stimulation (TES) has been considered a promising tool for improving working memory (WM) performance. Recent studies have demonstrated modulation of networks underpinning WM processing through application of transcranial alternating current (TACS) as well as direct current (TDCS) stimulation. Differences between study designs have limited direct comparison of the efficacy of these approaches, however. Here we directly compared the effects on WM of TACS to the frontal-parietal loop with TDCS applied to the dorsolateral prefrontal cortex, evaluating performance of a visual 2-back WM task. A within-subject design was applied (N = 30). Each participant underwent three separate sessions, receiving TACS, anodal TDCS, and sham stimulation in a counterbalanced order, and the WM task was performed before, during, and after stimulation. No significant difference in reaction times for hits (RT-hit) or accuracy was detected between application of TACS and TDCS with this study design. A marked practice effect was noted, however, with improvement in RT-hit irrespective of stimulation type, which peaked at the end of the second session. We observed that the pre-stimulation RT-hits in the third session returned to the same level as before stimulation in session two, irrespective of stimulation type, allowing the results of the second and third sessions to be pooled over the participants who received sham stimulation in session one. The pooling enabled a between-subject direct comparison between TACS and TDCS in a subgroup of participants (N = 10) in whom improvement due to practice alone, had reached a plateau. TACS resulted in a greater improvement in RT-hits than TDCS (F(2;18) = 4.31 p = 0.03). This study design, in which improvement in task performance due to practice had peaked before stimulation was applied, enabled a direct comparison between WM performance improvements following TACS and TDCS. Our findings suggest that optimizing the application of TACS has the potential to facilitate WM performance.